Assessment of Executive Function in Everyday Life—Psychometric Properties of the Norwegian Adaptation of the Children’s Cooking Task - Finnanger, Torun G.; Andersson, Stein; Chevignard, Mathilde; Johansen, Gøril O.; Brandt, Anne E.; Hypher, Ruth E.; Risnes, Kari; Rø, Torstein B.; Stubberud, Jan (Frontiers in Human Neuroscience, 2022)
Background: There are few standardized measures available to assess executive function (EF) in a naturalistic setting for children. The Children’s Cooking Task (CCT) is a complex test that has been specifically developed to assess EF in a standardized open-ended environment (cooking). The aim of the present study was to evaluate the internal consistency, inter-rater reliability and discriminant, convergent and divergent validity of the Norwegian version of CCT among children with pediatric acquired brain injury (pABI) and healthy controls (HCs). Methods: The present study has a cross-sectional design, with baseline data derived from a RCT. Seventy-five children with pABI from with parent-reported executive dysfunction and minimum 12 months since injury/completed cancer therapy as well as 59 HCs aged 10-17 years were assessed with CCT, using total errors as main outcome. The pABI group completed performance-based EF tests (i.e. inhibition, cognitive flexibility, working memory and planning) and EF questionnaires. Additionally, they completed tests of intellectual ability, processing speed, attention, learning and memory. Finally, overall functional outcome (Glasgow Outcome Scale-Extended) was evaluated for the children with pABI. Results: Acceptable internal consistency and good inter-rater reliability were found for the CCT. Discriminant validity was demonstrated, as children with pABI performed significantly worse on the CCT than the HCs. Convergent validity was demonstrated by associations between the CCT and performance-based tests assessing inhibition, cognitive flexibility and working memory, as well as teacher-reported executive dysfunction (questionnaires). Divergent validity was supported by lack of associations with performance-based measures of learning and memory, attention and verbal intellectual ability. However, there was a moderate association between the CCT and performance-based tests of processing speed. Lastly, better performance on the CCT was associated with a better functional outcome. Conclusion: Our study with a large sample of children with pABI and HC’s demonstrated good psychometric properties of CCT. CCT performance was related to the overall level of disability and function, suggesting that CCT is related to level of activity in everyday life and participation in the society. Hence, our study suggests that the CCT has the potential to advance the assessment of EF by providing a valid analysis of real-world performance.